Implementation of a New Geometrical Qualification (DQ) Method for an Open Access Fused Filament Fabrication 3D Printer - Belarbi, B.; Ghernaout, M. E. A.; Benabdallah, T. (Engineering, Technology & Applied Science Research, 2019)
This work presents geometric qualification on rapid prototyping process in the case of open access 3D printers where a working model is proposed and a prototype measurement is presented. The problem, which is to develop a methodological approach for the realization of five test pieces of equal dimensions based on complete process knowledge of the downstream material deposit movement according to XML standards, is addressed after a state of the art review. The result allows confirming the quality of the machine recommended by the manufacturer. Basically, the adopted methodology was used to fill the vacuum in the 3D FDM (open source) 3D geometric qualification (DQ) as well as to pave the way for the 3D printing processes standardization [1].